Extensively drug-resistant Acinetobacter baumannii lung abscess and empyema in a patient with fulminant mycoplasma pneumoniae pneumonia - Siyu Yang; Chaojie Wei (Respiratory Medicine Case Reports)
Acinetobacter baumannii is a pathogen that typically causes nosocomial infections. Its resistance to multiple antibiotics poses significant challenges for treatment. Fulminant Mycoplasma pneumoniae pneumonia (FMPP) is relatively rare despite Mycoplasma pneumoniae pneumonia is common among children and young adults. We present a case involving the concurrence of FMPP and lung abscess and empyema caused by extensively drug-resistant (XDR) A.baumanii. The patient was successfully treated through a novel and effective antibacterial regimen combined with timely drainage.